Beyond similarities and differences: Unveiling critical thinking in EFL students’ comparison-contrast essays - Ilyas, Hamzah Puadi; Tarmini, Wini; Ahmad, Zuhad (English Education Department, Universitas Islam Indonesia, 2026)
Critical thinking is widely recognized as a key objective in English as a Foreign Language (EFL) writing instruction. However, few studies have explored how it is demonstrated in specific academic genres. This study examined how EFL university students expressed critical thinking through the writing of comparison-contrast essays. Guided by Paul and Elder’s (2020) critical thinking framework, the study addressed the question: How do EFL students demonstrate critical thinking in the process of composing comparison-contrast essays? The research took place in an essay writing course at a university in Jakarta, Indonesia, involving 20 fifth-semester English education majors aged 21–23. Data included students’ essays and their written reflections on the writing process. The data were analyzed using qualitative content analysis, applying the elements and intellectual standards of critical thinking to identify patterns of reasoning. The findings showed that students demonstrated critical thinking through analytical categorization, evaluative judgments, integration of perspectives, and logical organization. Reflections revealed deliberate thinking strategies that supported the writing process. The study concludes that comparison-contrast writing, when paired with structured instruction and reflective practice, provides a productive platform for developing critical thinking. These insights contribute to genre-based writing pedagogy and support the integration of critical thinking as a central goal in EFL education